(untitled) (Al-Academy, 2018)
Despite the development in the fields of communication and informatics, the book remains its distinguished presence and popular popularity as it is the oldest means to obtain knowledge, addressing the vast majority of society in different levels and levels of knowledge and culture. The design of the cover book portal and the structure of semolina semantic including the elements of construction and typography contribute to the activation of the relationship between form and content, and here lies the importance of this relativity and its role in enhancing the communicative dimension of the design of the book cover, and cast a shadow on the promotional and marketing effectiveness. Hence the importance of research, but the problem of research was determined by the following question: Are the forms in the designs of book covers relational content? , And a goal to reveal the dialectic of the relationship between form and content through the expression of typographic elements. The research highlighted several topics (the form of book covers, the content and the semantic expressions in the design of the book cover). The researcher also chose the descriptive approach to analyzing (4) The research of (40) book cover issued by the House of Cultural Affairs, or 10%, and the most important results The designer adopted the method of symbolic expression in samples (1,2), the method of symbolic expression in the model (2), and the symbolic symbolic expression of the samples (3.4). The designer chose the drawings in the semantic semantic expression to investigate the relationship between form and content in favor of the industrial and marketing effort of the book, while the drawings (works of art) in sample (4) failed as a symbolic conveyor of the book’s content due to the semantic distortion, Functional format.